Personal protective equipment (PPE) during the COVID-19 pandemic for oculofacial plastic and orbital surgery. (4th July 2021) - Daigle, Patrick; Leung, Victoria; Yin, Vivian; Kalin-Hajdu, Evan; Nijhawan, Navdeep
ABSTRACT: Purpose : To review the current literature on Coronavirus Disease 2019 (COVID-19) virology and transmission; to present a decision tree for risk stratifying oculofacial plastic and orbital surgeries; and to generate personal protective equipment (PPE) recommendations by risk category. Methods : A comprehensive literature review on COVID-19 was conducted. A two-stage modified Delphi technique involving 18 oculofacial plastic and orbital surgeons across Canada was used to determine consensus risk-stratification criteria and PPE recommendations for surgeries performed in the North American context. Results : COVID-19 is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We summarize COVID-19 virology and transmission, as well as practice considerations for oculofacial plastic and orbital surgeons. Although SARS-CoV-2 is known to be transmitted predominantly by droplet mechanisms, some studies suggest that transmission is possible through aerosols. Among common procedures performed by oculofacial and plastic surgeons, some are likely to be considered aerosol-generating. Risk of transmission increases when manipulating structures known to harbor high viral loads. We present an algorithm for risk-stratification based on the nature of surgery and the anatomical sites involved and offer recommendations for PPE. Conclusions : Although universal droplet precautions are now recommended in most healthcare settings, some clinical situations require more stringent infection control measures. By highlighting high-risk scenarios specific to oculofacial plastic and orbital surgery, as well as PPE recommendations, we hope to enhance the safety of continued care during the COVID-19 pandemic.